Azulene‐based Hole Transport Materials with Proper Electronic Properties for Perovskite Solar Cells. Issue 10 (16th September 2022) - Su, Yangyang; Li, Haoyu; Miao, Yawei; Tian, Yi; Cheng, Ming
Abstract: With the advantages of adjustable structure and energy level, organic small molecules have been attracting much attention as hole transport materials (HTMs). Azulene was widely used in charge transfer materials for organic electronic devices. In this paper, two HTMs (Azu‐TPA and Azu‐OMeTPA) based on azulene core unit were synthesized by concise routes. Both Azu‐TPA and Azu‐OMeTPA demonstrate suitable molecular orbital energy levels as HTMs. Their hole mobility are over 10 −4  cm 2 V −1 S −1 and conductivity are over 10 −4  S cm −1, comparable with that of Spiro‐OMeTAD. Besides, they exhibit good hydrophobicity. Applied in PSCs, moderate power conversion efficiency (PCE) up to 15.41% was obtained. These results suggest the potential of azulene as a build block to develop HTMs with desirable electronic properties for perovskite solar cells (PSCs). Abstract : Azulene ‐based hole transport materials Azu‐TPA and Azu‐OMeTPA were synthesized by a concise route, both of them exhibit suitable frontier orbital energy levels, nice hole mobility and conductivity, good hydrophobicity. When applied in perovskite solar cells, moderate power conversion efficiency up to 15.41% was obtained.